Penyuluhan Hukum Tentang Pembentukan Peraturan Desa - Muhammad Irham; Natanel Lainsamputty; Garciano Nirahua; Ronny Soplantila (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The authority possessed by the village government in forming village regulations, in addition to the authority possessed by the village, in the administration of government in the village must be based on mutually established regulations. Counseling carried out in the Poka village with the consideration that if you look at the development of the formation of village regulations, there are still many obstacles faced, namely the limitations of human resources.Purposes of Devotion: Provide legal understanding of Establishment of village regulations in Poka Village, Teluk Ambon District, Ambon City. Method of Devotion: The method used is counseling law to the community, especially to the Poka village government and the Poka village BPD.Results of the Devotion: The implementation of these activities is known that there are many problems in the capacity to form village regulations, this has an impact on the administration of government which is only based on ordinary government management, without any breakthroughs in the formation of village regulations which are the basis for innovation in the development of poka village development.